Birth weight, childhood growth and menarche in South Africa - Paterson, Frances (My University, 2016)
Background and objectives Menarche serves an important marker of female health for individuals and populations. It indicates the onset of sexual maturation and reproductive capacity, but also serves as a prognostic factor for future growth, development, and the health of the individual and the population as a whole. Birthweight and childhood growth are thought to affect the age at menarche (AAM) through a number of different mechanisms but this relationship has yet to be fully explored. The objectives of this study were: 1. To describe the age of onset of menarche in a population of healthy ‘normal weight’ females in the Birth to Twenty cohort. 2. To demonstrate the influence of birth weight on the age of menarche 3. To assess the impact of childhood growth on the age of menarche 4. To assess the contribution of weight gain during specific periods in infancy and childhood on the age of menarche. Design, setting and participants Data from 788 South African children from the Birth to Twenty (Bt20) prospective birth cohort study who were followed prospectively throughout childhood were used. Variables included prenatal characteristics, birth measurements, serial measurement of height and weight during childhood, socio-economic status, and age at menarche. Exposures were weight at birth, then at 2 years, and 4 years; and conditional weight gain (CWG) between these ages. Outcome was age at menarche. Results: Age of onset of menarche: The average age of menarche in our sample was 12.66 years. Relationship between birthweight on age of menarche: The findings of this study show that birthweight does not significantly affect AAM Childhood growth and menarche: Our analysis shows a sustained and significant relationship between weight at 2 years, and weight at 4 years of age, with growth in the first 24 months having the greatest effect Conclusion: Increased weight gain in infancy during the first 24 and 48 months is associated with earlier AAM in girls. This has major implications for clinical practice especially in developing countries. There is currently a poor understanding of the underlying mechanisms underlying this phenomenon, and more research in this area is required to understand the interplay between environmental and genetic factors affecting the antenatal environment, childhood growth, and menarche.
A research report submitted to the Faculty of Health Sciences, University of the Witwatersrand, Johannesburg, In partial fulfilment of the requirements for the degree of Master of Medicine in Obstetrics and Gynaecology February 2016